Tribological characteristics of WC-based claddings using a ball-cratering method - Stachowiak, Grazyna; Stachowiak, Gwidon (Elsevier Ltd, 2010)
Tungsten carbide-based thick coatings are used as wear resistant claddings or surface overlays in industrial applications to counter erosive and/or abrasive wear problems. Three-body abrasive wear behaviour of infiltration brazed tungsten carbide (WC) claddings was investigated using a ball-cratering method, a version with a free ball, with slurry containing 150-300 µm silica sand particles. Three WC claddings tested had different volume fractions and size distribution of carbides that resulted in their different bulk hardness and the matrix was a Ni-Cr based alloy. It was found that the wear rates of all WC claddings were almost constant with testing time or distance travelled by a rotating ball. The wear rates were independent of the slurry delivery rate and did not increase with increasing rotating ball roughness. The wear rates were affected by the material characteristics of WC claddings such as the volume fraction of carbides, directly related to bulk hardness, and carbide size distribution. SEM examination found that three-body rolling wear was a dominating wear mechanism. The softer matrix was worn out preferentially, leaving behind protruding and weakly-supported carbides. Small solid carbides were then dislodged and larger cemented WC/Co carbides were gradually worn out by a combination of microcracking and attrition. The abrasive characteristics of WC claddings in the ball-cratering tests were then compared to the characteristics of nominally identical materials in the standard ASTM G65 and G76 tests, as reported in the literature, and similarities and differences found are reported. Also, the in-field wear mechanisms found in the WC cladding were compared to the mechanisms observed in the ball-cratering tests.